Ultrastructural changes of the digestive tract of Pomacea canaliculata exposed to copper at lethal concentration - Vipawee Dummee; Maleeya Kruatrachue; Sombat Singhakaew; Phanwimol Tanhan (Penerbit Universiti Kebangsaan Malaysia, 2021)
The present study was undertaken to elucidate the basis of cellular reactions and to verify the suitability of Pomacea canaliculata digestive tract ultrastructure as a biomarker for assessing the Cu pollution in freshwater environments. Two-month-old P. canaliculata were exposed to 96-h lethal concentration of Cu (0.15 mg L-1) for 96 h. Electron microscope investigations showed different alterations of organelles in the epithelial cells lining the esophagus and intestine. The most striking changes were damages to the mitochondria, RER, and nucleus typified by loss of cristae and degeneration of mitochondria; degranulation and fragmentation of RER. In nucleus, karyolysis and rupture of nuclear envelope were observed. These changes were attributed to membrane destabilization and increased membrane permeability to ions under the influence of toxicants or heavy metals. These findings indicate the possibility of using the P. canaliculata as biomonitor for Cu contamination in the freshwater environment.